Alih Aksara dan Alih Bahasa Kitab Takbir Mimpi dan Gempa - Pegi Aulia; Nurizzati Nurizzati (Jurnal Bahasa dan Sastra, 2020)
This research aimed to: (a) present a description of Takbir Mimpi dan Takbir Gempa script, (b) present the transliteration form Arabic-Malay into Latin script of Takbir Mimpi dan Takbir Gempa text, (c) present the translation from Malay-Minang into Indonesian language of Takbir Mimpi dan Takbir Gempa script. This research is included in the type of philological research. The object of his research is the text of theTakbir Mimpi dan Takbir Gempa. The method of this research is method of philology research which is adjusted with research stage and descriptive method. At the stage of data collection used the method of literature or observation, at the stage of the description of the manuscript used a descriptive method, the stage of transliteration used the method of transliteration or the method of transliteration, then the stage of language transfer used the method of language transfer. The results of this research were (1) the complete description of the script, (2) the transcription of Takbir Mimpi dan Takbir Gempa text from Arabic-Malay into Latin without changing the kind of language that can be read and understood by the present society(3) Takbir Mimpi dan Takbir Gempa text had adapted into correct Indonesian Spelling (EBI). Some of Malay’s vocabularies and Minangkabau language’s vocabularies found in Takbir Mimpi dan Takbir Gempa script were maintained to preserve the purity of the old vocabulary.